Flow pathways in multiple-direction fold hinges: Implications for fractured and karstified carbonate reservoirs. (May 2021) - Pontes, Cayo C.C.; Bezerra, Francisco H.R.; Bertotti, Giovanni; La Bruna, Vincenzo; Audra, Philippe; De Waele, Jo; Auler, Augusto S.; Balsamo, Fabrizio; De Hoop, Stephan; Pisani, Luca
Abstract: Caves developed in carbonate units have a significant role in fluid flow, but most of these subsurface voids are below seismic resolution. We concentrated our study on four caves to determine the roles of fractures and folds in the development of karst conduits that may form flow pathways in carbonate reservoirs. We performed structural field investigations, petrographic analyses, and geometric characterization using Light Detection and Ranging (LIDAR) for caves in Neoproterozoic carbonates of the Salitre Formation, central part of the São Francisco Craton, Brazil. We found that the conduit shape, usually with an ellipsoidal cross-section, reflects the tectonic features and textural variations. Carbonate layers containing pyrite and low detritic mineral contents are generally karstified and appear to act as favorable flow pathways. Our results indicate that the development of the karst system is related to fracture corridors formed along parallel and orthogonal sets of fold hinges, which provide preferential pathways for fluid flow and contribute to the development of super-K zones. This study provides insights into the prediction of subseismic-scale voids in carbonate reservoirs, with direct application for the hydrocarbon and hydrogeology flow and storage. Graphical abstract: Image 1 Highlights: We study fracture corridors and karst flow pathways on a subseismic scale. We use LiDAR imagery to qualify and quantify deformation and karst geometry. Hypogene karst development is related to localized rather than diffuse deformation. Karst formed in carbonate units affected by multiple-direction fold hinges.